PENGARUH KONSENTRASI DAN FREKUENSI PEMBERIAN GIBERELIN TERHADAP PERTUMBUHAN TANAMAN ARTEMISIA ANNUA Linn - Fransisca Mareta Kurnia Sari; Maria Marina Herawati; Endang Pudjihartati; Martinus Andree Wijaya Setiawan (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2022)
Artemisia is one of the plants that can be used as an alternative medicine for malaria. The Artemisia plant contains secondary metabolites in the form of artemisinin compounds that function as antimalarials. One of the efforts that can be done to increase the growth of Artemisia annua. plants is by using a growth regulator of gibberellins (GA3). Using a Randomized Block Factorial Designs (RBFD) with the first factor being the concentration of 50 mg.L-1 (K1), mg.L-1(K2), 150 mg.L-1 (K3), 200 mg.L-1 (K4). The second factor has 3 frequencies, 1 time giving 7HSPT (F1), 2 times giving 7HSPT and 14HSPT (F2), and 3 times giving 7HSPT, 14HSPT and 30HSPT (F3). In addition, there were plants that were not given GA3 control (without treatment). Parameters observed were plant height, leaf area, glandular trichome density, and plant dry weight. The results showed that the administration of gibberellins (GA3) with different concentrations and frequencies on plant height, leaf area, glandular trichome density, and dry weight of A. annua plants had no significant effect. Plants have not been able to grow properly because the provision of gibberellins that have not been active stimulates all plant tissues and directly seeps through the roots, stems and leaves.